IDENTIFIKASI PENGGUNAAN OBAT PADA PASIEN HIPERTENSI USIA LANJUT DENGAN BEER’S CRITERIA DI INSTALASI RAWAT INAP RUMAH SAKIT IBNU SINA MAKASSAR PERIODE TAHUN 2012 - Sukmawati, Sukmawati; Kosman, Rachmat; Damayanti, Ira (Jurnal Ilmiah As-Syifaa, 2016)
Identification in the use medicine in geriatric patient of hypertension with Beer's Criteria In inpatient installation of Ibnu Sina Makassar hospital period 2012. In this study aims to observe and report on the use of drugs included in the Beers criteria on the use medicine in geriatrics patients of hypertension in the inpatient of Ibnu Sina Makassar Hospital. This is an observational study with the following descriptive design through the entire medical record in geriatrics patients who suffer from hypertension of Ibnu Sina Hospital in Makassar. The results showed that the types of drugs included in the Beers criteriaare nifedipine (3.44%), alprazolam (44.82%), lorazepam (13.79%), diazepam (13.79), estazolam (6.89 %), metokloperamide (10.34%), and mefenamic acid (3.44%).